The Correlation between Direct Instruction and Speaking Skill: A Quantitative Study on Grade XI Teknik Elektronika Industri Students of SMK Negeri 2 Pekanbaru - Anfilla Tahany; Siti Niah; Puan Liyana Binti Ahmad Afip (Jurnal Pendidikan dan Sastra Inggris, 2025)
This study aims to analyze the correlation between the implementation of the Direct Instruction model and students’ speaking skills among eleventh-grade students majoring in Electronics Engineering at SMK Negeri 2 Pekanbaru. The research employed a quantitative correlational design to determine the strength and direction of the relationship between the two variables. Data were collected using two instruments: the Direct Instruction Questionnaire to assess the extent of the instructional model’s application and the Speaking Skill Test to evaluate students’ oral performance. The collected data were then analyzed using the Pearson Product Moment correlation technique. The results of the hypothesis testing revealed a significance value (2-tailed) of 0.000, which is lower than 0.05, indicating that the null hypothesis (H₀) is rejected and the alternative hypothesis (Hₐ) is accepted. This finding demonstrates a statistically significant relationship between Direct Instruction and students’ speaking skills. Moreover, the correlation coefficient of 0.552 shows that the strength of the correlation falls within the “moderate” category. These results suggest that the more effectively the Direct Instruction model is implemented, the better students’ speaking performance tends to be. Thus, Direct Instruction can be considered a useful and structured approach to enhance students’ speaking ability in vocational education settings.